Physicochemical properties, sensory characteristics, and volatile compounds of Indonesian traditional drink (Sarabba) - Syarifuddin, Adiansyah; Azizah, Nurul; Dirpan, Andi (Food Science and Technology, 2023)
Abstract: ‘Sarabba’ is a popular traditional drink that is mostly consumed in South Sulawesi Province, Indonesia. ‘Sarabba’ has been known for its health benefits because its ingredients contain some spices, but this drink has been poorly studied. This study aimed to characterise the physicochemical properties, sensory perception, and volatile compounds of ‘Sarabba’. The importance of this study was to provide valuable insight for small-scale manufacturers on how the use of chicken egg yolk and sweetened condensed milk can affect the physicochemical properties and perception of Sarabba. Physicochemical properties, including colour, protein content, total soluble solid, pH, viscosity, and sensory evaluation from Sarabba, Sarabba with chicken egg yolk, and Sarabba with sweetened condensed milk, were performed in this study. Volatile compounds extracted by solid-phase microextraction and analysed by gas chromatography-mass spectrometry were also performed. The results showed that Sarabba with egg yolk has the highest protein content and viscosity, whereas 99 volatile compounds were found in Sarabba with sweetened condensed milk. The most common chemical groups identified in all Sarabba include terpenes, alcohols, ketones, ester, and alkanes. The addition of egg yolk and sweetened condensed milk could affect physicochemical properties and increase volatile compounds while maintaining the liking of ‘Sarabba’.